Comparative effects of post isometric relaxation and active release technique of calf muscles in young females; Randomized Clinical Trial - Zuha Javed; Safdar, Maryam (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the effects of post-isometric relaxation and active release techniques in terms of pain, range of motion and functional disability on calf muscles in young females. Method: The randomised clinical trial was conducted from February to May, 2024, at the Allied Hospital, Faisalabad, Pakistan, and comprised females aged 20-40 years who presented with functional disability due to calf tightness. The patients were randomised using the lottery method into groups A and B. Both the groups received a moist hot pack at baseline, and calf strengthening exercises at the end of treatment. Group A received post-isometric relaxation by adding 20% effort of the patient in a supine lying position. Group B received active release technique on calf muscles in a prone position. There were two sessions per week for four weeks. Pain was measured using the visual analogue scale, and range of motion was measured with a universal goniometer. The secondary outcome was functional disability due to calf tightness, which was assessed using the Lower Extremity Functional Scale. Data was analysed using SPSS 27. Results: Out of the 40 patients initially screened, 30(75%) were randomised into the two groups. However, the study was completed by 27(90%); 13(48.15%) in group A with mean age 29.15± 4.59 years, and 14(51.85%) in group B with mean age 29.35±4.41 years. Three variables pain, range and functional disability were measured. When data were interpreted, there were significant improvement in both groups compared to baseline values within groups but there was no significant difference between the groups with respect to outcome measures (p>0.05). Conclusion: The post-isometric relaxation and active release techniques were found to be equally effective in terms of pain, range of motion and functional disability related to calf muscles in young females. Key Words: Females, Range of motion, Visual analogue scale.